"Body on the line": experiences of tackle injury in women s rugby union a grounded theory study - Wilson, Fiona; Foley, Geraldine (My University, 2023)
Objectives Tackle-related injuries account for up to 67% of all match injuries in women’s rugby union. The perspective of women players on tackle injury can help key stakeholders understand psychosocial determinants of tackle injury risk and prevention. We aimed to capture psychosocial processes that explain tackle injury experiences and behaviours in women’s rugby union. Methods We conducted a qualitative study using a grounded theory approach. Adult women players, with at least 1-year senior level experience, were recruited from Europe, South Africa and Canada between December 2021 and March 2022. Data were collected through semistructured interviews and analysed in line with grounded theory coding procedures. Results Twenty-one players, aged 20–48 years with a mean 10.6 years of rugby playing experience, participated. In our analysis, we identified three categories central to participants’ experiences of tackle injury: (1) embodied understandings of tackle injury, (2) gender and tackle injury risk and (3) influences on tackle injury behaviours. Participants reported a sense of fear in their experience of tackling but felt that tackle injuries were an inevitable part of the game. Tackle injury was described based on performance limitations. Tackle injury risks and behaviours were influenced by gendered factors perpetuated by relations, practices and structures within the playing context of women’s rugby union. Conclusion Women’s tackle injury experiences were intertwined with the day-to-day realities of marginalisation and under preparedness. Grounded in the voices of women, we have provided recommendations for key stakeholders to support tackle injury prevention in women’s rugby.
PUBLISHED
Keywords: Tackle-related injuries; Rugby; Women's health; Injury prevention; Sports Medicine; female sport; rugby